SENI GRAFIS YOGYAKARTA DALAM WACANA SENI KONTEMPORER - Wiwik Sri Wulandari (Ars: Jurnal Seni Rupa dan Desain, 2008)
Visual art in Indonesia is not stagnant at all. It is because art always respond to the complex world development from time to time. Graphical Art in Yogyakarta has been developing as well. It always contributes to the visual art promotion of Indonesia. This article will focus on exploring the movement of Graphical Art in Yogyakarta in the frame of Indonesia contemporary art discourse. The Graphical Art in Yogyakarta has been metamorphosing both in visual and conceptual aspects in line with the latest development of the contemporary art.Keywords: graphical art, contemporary art, alternative discourse